Hannevi'ah and Hannah : hearing women Biblical prophets in a woman's lyrical tradition - Lee, Nancy C. (Cambridge, United Kingdom : James Clarke & Co, 2016)
Based on careful analysis of the lyrical traditions of ancient Hebrew, this challenging study reveals methods of discerning previously unnoticed female voices within Old Testament prophetic texts.
Includes bibliographical references.
Vendor-supplied metadata.
Master record variable field(s) change: 050, 072, 082
Keywords: Women in the Bible; Women prophets; Women in the Bible; Women prophets; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books